Reducing Complexity by Creating Complexity: A Systems Theory Perspective on How Organizations Respond to Their Environments - Schneider, Anselm; Wickert, Christopher; Marti, Emilio (Journal of management studies, 2017)
Organizations have to cope with the complexity of their environment in order to survive. A considerable body of research has shown that organizations may respond to environmental complexity by creating internal complexity – for example, by expanding internal structures and processes. However, researchers know less about how organizations create collaborative complexity collectively – for example, by establishing alliances or developing common standards. This paper uses social systems theory to explore how organizations collaborate in response to complexity and to analyse the conditions under which they create either internal or collaborative complexity (or both) to address environmental complexity. It also examines how these types of complexity feed back into environmental complexity. To illustrate our conceptual model, we use corporate social responsibility (CSR).